Strengthening the Foundations of Socialpreneurship through Integrated Reporting A Systematic Bibliometric Perspective - Anna, Yane Devi; Djajadikerta, Hamfri; Setiawan, Amelia (Pandawan, 2026)
Concerns regarding the limitations of traditional financial reporting and the narrow focus on shareholder value have led to growing interest in Integrated Reporting (IR), which aims to improve information quality for stakeholders and support sustainability. This study investigates the development of research on Integrated Reporting Quality (IRQ), including its theoretical foundations, measurement methods, influencing factors, and the role of IR in supporting socialpreneurship. Using a systematic literature review and bibliometric analysis of 53 selected articles from 2021 to 2025, and guided by PRISMA methodology, the study explores trends, theories, and keyword networks within IRQ research. The findings reveal key theoretical lenses such as agency, stakeholder, and legitimacy theories, and identify widely used measurement tools like the IR Scoreboard. Furthermore, the study demonstrates how high-quality IR can enhance transparency, attract impact investors, and foster sustainable value creation in social enterprises. Overall, this research provides valuable theoretical insights and practical recommendations for improving IRQ and underscores its strategic importance in advancing sustainability and accountability in socialpreneurship.